Hierarchical Assembly of Carbon Dots with Full‐Solar‐Spectrum Absorption for Solar Energy Applications - Lei Li; Di Li; Yanfei Qu; Ruoyu Zhang; Shuo Qi; Mengyao Liu; Haohao Bi; Tao Jia; Songnan Qu; Weitao Zheng (Advanced Science)
Abstract Carbon dots (CDs) featuring low‐cost, non‐toxic, and appealing optical properties demonstrate promising applications in energy, e.g. solar energy capture and conversion. However, it remains a significant challenge to expand the absorption bands of CDs from visible to near‐infrared (NIR) spectral regions to harness the entire spectrum of sunlight for efficient solar energy utilization. Herein, hierarchical assemblies of CDs (HA‐CDs) are constructed by stepwise assembling monodispersed ultraviolet‐absorbing CDs to water‐soluble visible‐NIR absorbing supra‐CDs (PA‐CDs), and then complexing PA‐CDs with Fe3+ ions to form 3D porous architectures (HA‐CDs) with full solar spectrum absorption and good water resistance. Notably, the HA‐CDs exhibit good hydrophilicity and superior photothermal conversion efficiency of 84% under simulated solar irradiation. The facile Fe3+ ion cross‐linking assembly property enables the in situ preparation of HA‐CDs on various fabric substrates, resulting in low‐cost, high‐performance photothermal conversion products. High‐performance 2D solar‐driven interfacial water evaporation, electricity generation, and water‐electricity cogeneration have been demonstrated in the HA‐CDs in situ coated fabric (HA‐CDs‐fabric). This study provides a novel and effective design approach for the development of high‐performance CD‐based photothermal materials for solar energy applications.